TELAAH QIRA’AT QS. AL-BAQARAH AYAT 229 DAN RELEVANSINYA TERHADAP HUKUM KHULU’ MENURUT AL-ZAMAKHSYARĪ - Ahmad Raihan; Muhammad Azhari; Matsna Zuhal Muftiuddin; Najib Irsyadi (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
Abstract This article examines the concept of khulu’ in the perspective of the classical interpretation of al-Kasysyāf by al-Zamakhsyarī, focusing on linguistic and qirā’at analysis of the phrase “an yakhāfā” in QS. al-Baqarah [2]:229. Through a qualitative-descriptive approach based on literature study, this article highlights the relationship between the various readings of qira’at and their implications for Islamic family law, especially in providing legal space for women to exit problematic marriages. Al-Zamakhsyarī’s interpretation that emphasizes the balāghah dimension and the rationality typical of the Mu’tazilah provides an alternative perspective in understanding the law of khulu’. The findings show that variations of qirā’at such as “yukhāfā”, “takhāfū”, and “yazunnā” have an important influence on the formation of law, which opens up space for ijtihad and a contextual approach to the sacred text. This article emphasizes the relevance of linguistic interpretation in the effort to reform Islamic family law to be more just and beneficial